Challenges and Protection Strategies for Rivers and Lakes - Zhang, Jinsong (Transactions on Environment, Energy and Earth Sciences, 2024)
Rivers and lakes play a crucial role in freshwater supply, maintenance of ecosystems, and the sustainability of humans’ society, economic activities and culture. However, these water bodies are often threatened by pollution, damming, and over-extraction, causing a series of problems for ecosystems and communities. The paper analyzes the challenges faced by rivers and lakes and proposes some measures to deal with these problems. The major challenges include the spread of pollutants, eutrophication, abnormal flow regulation, and lowering water levels, which lead to the loss of biodiversity, threat to human health and economic activities, and the collapse of culture and civilization. This study proposes solutions based on technologies and policies. The technique solutions include Variable Rate Technology and Precision Irrigration System for precision farming and buffer zones for water treatments. For the government, the withdrawal policies for water should be applied to prevent agricultural and industrial overuse and waste of water resources. Besides, the coordinated work between upstream and downstream communities and the participation of the government matters a lot to the conservation of rivers and lakes and the preservation of the cultural and historical legacies related to these water bodies.